In vitro study of differentiation of cells derived from embryonal and postnatal brain - Semionova, V. M.; Lisyany, N. I.; Lyubych, L. D.; Petrenko, A. Yu.; Stayno, L. P. (Ukrainian Neurosurgical Journal)
The influence of the range of biopreparats on the neuronal differentiation cytostructural peculiarities of the cultivated neural precursors derived from rats’ embryonal brain and human cryopreserved neurocells was studied. The cultivation in vitro of neuronal precursors in DMEM without serum with addition of insulin-transferrin-selenit didn’t lead to their terminal differentiation. Under consequentional co-influence of insulin and retinolacetate on the neural cell cultures about 8,5% of cells undergo the neuronal differentiation, while cultivation with retinoic acid stimulate the growth of number of differentiated cells to 20-30%. The obtained results evidence for the saved capacity of neuronal differentiation of cell precursors derived after long-term cultivation in suspension in DMEM.